Chernobyl (Sydney : BBC Enterprises Ltd., 1989)
Radiation experts visit the site of the worst nuclear accident. From the area immediately around the plant, 135,000 people were evacuated - but how are the villagers outside this zone learning to live with radioactivity? What are likely to be the long-term effects? And what has been learnt to ensure that such a disaster will never happen again
Copy available in DVD format
Copy available in DVD format
Keywords: Chernobyl Nuclear accident, Chernobyl', Ukraine, 1986 -- Social aspects